Execution of State Seized Property Based on Corruption Conviction Court Decisions Later Burdened with Bank Liens - Abvianto Syaifullah; Didik Endro Purwoleksono; Taufik Rachman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
One of the elements in the crime of corruption is the loss of state finances or the state economy, so that this element is the background for the formation of legislation regarding corruption crimes, both the old regulation, namely Law Number 3 of 1971 and the new regulation, namely Law Number 31 of 1999 concerning Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes which establishes a policy that state financial losses must be returned or replaced by the perpetrators of corruption (asset recovery). When the goods confiscated by the state are free or not encumbered by property guarantees, they can be directly executed by the Prosecutor in accordance with statutory provisions, but legal problems occur when the assets confiscated by the state turn out to be later encumbered by Mortgage Rights by the Bank/creditor after a court decision which in its verdict is "confiscated by the state" because the investigator does not apply for recording of criminal confiscation to the local State Land Agency. This type of research is normative or doctrinal research using a statutory approach and an asset forfeiture concept approach. The results of the research are that the Investigator is obliged to apply for the recording of criminal confiscation to the local State Land Agency regarding the object of the confiscated land, this aims to prevent it from being transferred to other parties or encumbered by Mortgage Rights. The need for the immediate enactment of the Asset Forfeiture Bill in order to recover state losses by perpetrators of corruption through in rem asset forfeiture so that assets that have been transferred or transferred by the perpetrator to other parties can still be confiscated by the state as a decision that has been legally binding (inkrah).